2020
DOI: 10.2478/acph-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

The controversies of parabens – an overview nowadays

Abstract: Effects of paraben toxicity, i.e., endocrine-disruption properties, are in the focus of researchers for decades, but still – they are a hot subject of debate. Parabens are aliphatic esters of p-hydroxybenzoic acid, which are widely used as antimicrobial agents for the preservation of cosmetics, pharmaceuticals and foods. Mostly used parabens are methyl-, ethyl-, propyl- and butylparaben. Although the toxicity of parabens is reported in animals and in in vitro studies, it cannot be taken for granted when discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 58 publications
0
48
0
Order By: Relevance
“…The first of them is the fact that PBs with short-chain functional groups (such as MePB, EtPB and PrPB) are present in the human organism in the highest concentrations, and therefore their adverse effects may have the most important influence on human health status. This is because such parabens are the most commonly used in the industry, which leads to relatively high environmental pollution with these substances 1 , 20 . The second observation is that the human body is exposed simultaneously to some PBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of them is the fact that PBs with short-chain functional groups (such as MePB, EtPB and PrPB) are present in the human organism in the highest concentrations, and therefore their adverse effects may have the most important influence on human health status. This is because such parabens are the most commonly used in the industry, which leads to relatively high environmental pollution with these substances 1 , 20 . The second observation is that the human body is exposed simultaneously to some PBs.…”
Section: Discussionmentioning
confidence: 99%
“…For decades PBs were considered to be completely safe for living organisms, but since the end of the twentieth century more and more studies have reported their adverse effects on humans and animals. Currently PBs are classified as endocrine disruptors, which have genotoxic and cytotoxic effects 15 , 16 and affect many internal organs and systems, mainly including the reproductive, immune and endocrine systems 17 20 . Some studies have also reported correlations between PBs and obesity, disorders in the nervous system developmental disorders and neoplastic processes 11 , 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Parabens belong to a group of esters of p-hydroxybenzoic acid. They have antibacterial and antifungal properties, therefore they are used as preservatives in personal care products, cosmetics, foodstuffs and some pharmaceuticals (55)(56)(57). They show weak estrogenic effect in vitro (57).…”
Section: Parabensmentioning
confidence: 99%
“…Another antimicrobial agent, paraben mixture (propyl and methyl parabens) is as well under the public eye as endocrine disruptors and allergen, where its influence on health is continuously examined [27,28]. EMA and Serbian regulations require appropriate labeling of these EKE as well as stating possible ADRs, which was satisfied in examined formulation SmPC.…”
Section: Wwwhophonlineorgmentioning
confidence: 99%